Penulisan Artikel Ilmiah Bereputasi Bagi Guru Sekolah Dasar Kota Padang - Erpidawat; Susi Yuliastanty; Hazlif Nazif (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
Requirements for teacher rank, especially in Group IVa to IVb, require special requirements, namely one journal published with ISSN both nationally and locally, in this case there are still many teachers who do not understand how to write an article taken from an existing PTK. The purpose of this service is to provide training to elementary school teachers in Padang City in writing reputable scientific articles. Until now there are still many Padang City elementary school teachers who have remained in group IVa and even for years now there are mandatory requirements that must be met for credit scores from the sub-element of scientific publications and/or elements of innovative work. The results obtained from this workshop are increasing teachers' understanding of writing reputable scientific papers and producing scientific papers from teachers.